Humanized mice in studying efficacy and mechanisms of PD‐1‐targeted cancer immunotherapy. Issue 3 (3rd January 2018) - Wang, Minan; Yao, Li‐Chin; Cheng, Mingshan; Cai, Danying; Martinek, Jan; Pan, Chong‐Xian; Shi, Wei; Ma, Ai‐Hong; de Vere White, Ralph W.; Airhart, Susan; Liu, Edison T.; Banchereau, Jacques; et al.
Abstract : Establishment of an in vivo small animal model of human tumor and human immune system interaction would enable preclinical investigations into the mechanisms underlying cancer immunotherapy. To this end, nonobese diabetic ( NOD).Cg‐Prkdc scid IL2rg tm1Wjl /Sz (null; NSG) mice were transplanted with human (h)CD34 + hematopoietic progenitor and stem cells, which leads to the development of human hematopoietic and immune systems [humanized NSG (HuNSG)]. HuNSG mice received human leukocyte antigen partially matched tumor implants from patient‐ derived xenografts [PDX; non ‐small cell lung cancer (NSCLC), sarcoma, bladder cancer, and triple‐negative breast cancer (TNBC)] or from a TNBC cell line‐derived xenograft (CDX). Tumor growth curves were similar in HuNSG compared with nonhuman immune‐engrafted NSG mice. Treatment with pembrolizumab, which targets programmed cell death protein 1, produced significant growth inhibition in both CDX and PDX tumors in HuNSG but not in NSG mice. Finally, inhibition of tumor growth was dependent on hCD8 + T cells, as demonstrated by antibody‐mediated depletion. Thus, tumor‐bearing HuNSG mice may represent an important, new model for preclinical immunotherapy research.—Wang, M., Yao, L.‐C., Cheng, M., Cai, D., Martinek, J., Pan, C.‐X., Shi, W., Ma, A.‐H., De Vere White, R. W., Airhart, S., Liu, E. T., Banchereau, J., Brehm, M. A., Greiner, D. L., Shultz, L. D., Palucka, K., Keck, J. G. Humanized mice in studying efficacy and mechanisms of PD‐1‐targeted cancer immunotherapy. FASEB J. 32, 1537 ‐1549 (2018). www.fasebj.org